The relationship between personality type and self-control with cyberbullying behavior in adolescents - Dzunnuroin, Naura Royyani; Julianingrum, Peni Perdani; Rahmawati, Ira (Pediomaternal Nursing Journal, 2023)
Introduction: Personality type and self-control are internal factors that can determine the behaviour of adolescents, one of which is cyberbullying. Personality determines the nature of adolescents, and self-control is the control of adolescents in holding back their responses and emotions to show behaviour. This study aimed to determine the relationship between personality type and self-control with cyberbullying behaviour in adolescents at Y High School Banyuwangi Regency.Methods: The research method used is quantitative with a cross-sectional approach design. This study was conducted on 196 adolescents using a purposive sampling technique with several inclusion criteria: active students aged 15 to 17 years, users of smartphones, email, and social media. The data were collected by using several measuring instruments: the Eysenck Personality Questionnaire (EPQ) with a reliability test value of α = 0.762, the Brief Self Control Scale with a reliability test value using a T-test with r = 0.18, and the Cyber Aggressore Scale (CYB-AGS) with reliability test value α = 0.867. Logistic regression statistical tests analyzed the data. Results: This study revealed no relationship between personality type and cyberbullying behavior with p-value = 0.573 and a relationship between self-control and cyberbullying behaviour with p-value <0.001.Conclusions: There is no relationship between personality type and cyberbullying behaviour, and there is a relationship between self-control and cyberbullying behaviour at Y High School Banyuwangi Regency. Keywords: cyberbullying; personality type; self-control